GENDER EQUALITY POLICY IN PUBLIC SECTOR HUMAN RESOURCE MANAGEMENT - I.V. Honcharenko; N.O. Shyshpanova (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu)
The topic of the article is dedicated to studying the integration of gender equality into the field of human resource management in the public service in Ukraine and the European Union countries. The purpose of the research is to examine modern approaches to ensuring gender equality, as well as to formulate practical recommendations for improving the implementation of its principles in public administration. The main goal is to identify existing problems and barriers that hinder the realization of gender equality in the public sector and to determine ways to overcome them.